Alienasi Karl Marx dalam Cerpen Surau di Sebelah Masjid Karya Raudah Jambak: Ketika Tradisi Tergusur oleh Modernisasi - Daely, Apriliani; Simanjuntak , Korintus; Etami, Wina (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This article aims to analyze the phenomenon of alienation that occurs in the short story Surau di Sebelah Masjid by Raudah Jambak through the perspective of Karl Marx’s alienation theory. Modernization that has penetrated the lives of traditional communities has caused social and cultural alienation marked by the loss of spiritual values and the breakdown of social relations. Using a sociology of literature approach and qualitative analysis methods, this study found that the alienation experienced by the characters in the short story reflects four forms of alienation according to Marx, namely alienation from the results of work, the work process, fellow human beings, and oneself. The results of this study indicate that modernization not only brings material changes, but also triggers an identity crisis and the loss of social solidarity in a society that adheres to tradition.